Zainteresirana slovenska javnost o pomenu gozda in gozdarstvu - Golob, Aleksander (Gozdarski vestnik, 2008)
The article presents the results of an inquiry conducted among 553 participants of the public debate on the Slovenian national forest program including visitors of the internet site which offered information about this program. The participants, half of whom were forest owners, are considered representatives of the public interested in forests and forestry. This public understands wood production as the most important individual aspect of forests, but considers environmental forest functions to be the most importantgeneral aspect; they are followed by production and social functions.Close-to-nature forest management is considered the most important advantage of the actual forest policy and free access to all forests also stands very high. The lack of active attitude to forests, especially low levelof tending is regarded as a most important weakness of actual forest management. The interested public would also want more information on forests and believes the level of research and education about forests is not adequate.
Keywords: gozdno gospodarstvo; javno mnenje; ankete